Military Position Transition In Every Era Of Indonesian Head Of State Leadership - Muhammad Budiana; Yusa Djuyandi (Universitas Sultan Ageng Tirtayasa, 2022)
The position of the military in taking on a political role in Indonesia has changed along with the changing leadership of the state. The dynamics of this change were born because of the pattern of civil-military relations in Indonesia. This civil-military relationship can be created when a concept called